2022
DOI: 10.1186/s12967-022-03767-z
|View full text |Cite
|
Sign up to set email alerts
|

Innate immunity, cytokine storm, and inflammatory cell death in COVID-19

Abstract: The innate immune system serves as the first line of defense against invading pathogens; however, dysregulated innate immune responses can induce aberrant inflammation that is detrimental to the host. Therefore, careful innate immune regulation is critical during infections. The coronavirus disease 2019 (COVID-19) pandemic is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and has resulted in global morbidity and mortality as well as socio-economic stresses. Innate immune sensing of SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 202 publications
(318 reference statements)
4
40
0
Order By: Relevance
“…There are numerous infectious and inflammatory causes of SIRS in the ICU and once diagnosed, additional acute pathological insults (along with co‐morbid diseases) can lead to a deteriorating clinical state as a consequence of an exuberant SIRS “cascade” with increased mortality 2 . Critically ill patients with severe acute respiratory distress syndrome and COVID‐19 infection often exhibit such a heightened hyper‐inflammatory state accompanied by a “cytokine storm.” 3 As the name implies, a cytokine storm is fueled by very high blood concentrations of multiple cytokines and chemokines, secreted by activated monocytes and macrophages response to the infectious or inflammatory insult. In addition, multisystem inflammatory syndrome in children (MIS‐C) shares many of the hallmark signs and symptoms, as well as treatment strategies for severe COVID‐19 infection, and is also believed to be a “postinfectious complication of SARS‐CoV‐2.” 4 Moreover, a recent hypothesis suggests that a viral “superantigen” in the spike protein of SARS‐CoV‐2 appears to trigger toxic shock syndrome in severe COVID‐19 infection and MIS‐C 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous infectious and inflammatory causes of SIRS in the ICU and once diagnosed, additional acute pathological insults (along with co‐morbid diseases) can lead to a deteriorating clinical state as a consequence of an exuberant SIRS “cascade” with increased mortality 2 . Critically ill patients with severe acute respiratory distress syndrome and COVID‐19 infection often exhibit such a heightened hyper‐inflammatory state accompanied by a “cytokine storm.” 3 As the name implies, a cytokine storm is fueled by very high blood concentrations of multiple cytokines and chemokines, secreted by activated monocytes and macrophages response to the infectious or inflammatory insult. In addition, multisystem inflammatory syndrome in children (MIS‐C) shares many of the hallmark signs and symptoms, as well as treatment strategies for severe COVID‐19 infection, and is also believed to be a “postinfectious complication of SARS‐CoV‐2.” 4 Moreover, a recent hypothesis suggests that a viral “superantigen” in the spike protein of SARS‐CoV‐2 appears to trigger toxic shock syndrome in severe COVID‐19 infection and MIS‐C 5 …”
Section: Introductionmentioning
confidence: 99%
“…2 Critically ill patients with severe acute respiratory distress syndrome and COVID-19 infection often exhibit such a heightened hyper-inflammatory state accompanied by a "cytokine storm." 3 As the name implies, a cytokine storm is fueled by very high blood concentrations of multiple cytokines and chemokines, secreted by activated monocytes and macrophages response to the infectious or inflammatory insult. In addition, multisystem inflammatory syndrome in children (MIS-C) shares many of the hallmark signs and symptoms, as well as treatment strategies for severe COVID-19 infection, and is also believed to be a "postinfectious complication of SARS-CoV-2."…”
Section: Introductionmentioning
confidence: 99%
“…It is still unclear, however, whether long COVID reflects the tissue persistence of the virus or is promoted by an aberrant inflammatory autoimmune response or by the primary organ damage triggered by the acute infection [ 9 ]. It has also been suggested that cellular damage, a robust innate immune response with inflammatory cytokine production, and a procoagulant state induced by SARS-CoV-2 infection may contribute to the pathogenesis of long COVID [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The innate immune system functions as the first line of defense against SARS-CoV-2; however, dysregulated innate immune responses can induce aberrant inflammation, cytokine storm, tissue damage, and acute respiratory distress syndrome in the host ( Karki and Kanneganti, 2022 ). We found that anti-svRNA 1 treatment, which recovers SERINC5, lowers the induction of innate immune-related genes (IFNβ, ISG20 and CCL20; Figure 9 ; Supplementary Figure S5 ), indicating that SERINC5 acts as a negative regulator of these genes during SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%